Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2017)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone(A (R))-KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone-KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine-Oxone as an unprecedented catalyst-oxidant combination. [GRAPHICS] .
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using Oxone as an oxidant (vol 43, pg 6875, 2017) - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2018)

Erratum to: catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V. (Research on Chemical Intermediates, 2018)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone®–KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone–KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine–Oxone as an unprecedented catalyst–oxidant combination.
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides